Geochemistry of basalt lavas from Vestfjella and adjacent areas, Dronning Maud Land, Antarctica - Furnes, Harald; Vad, Erik; Austrheim, Håkon; Mitchell, John G.; Garmann, Leif B. (Lithos, 1987)
K-Ar ages, major- and trace-element compositions, and Sr-isotope data are presented for basalt lavas from Vestfjella, Dronning Maud Land, Antarctica. The new conventional K-Ar age data have yielded ages from 171 ± 2 to 695 ± 11 Ma, but the youngest (i.e. Middle Jurassic) ages are preferred. Mineralogical and chemical data show that the majority of the basalts are tholeiites. Petrographic mixing calculations, REE modelling, and the Sr isotope data suggest that they were derived by partial melting of garnet-free lherzolites with variable REE patterns, and subsequently modified by fractionation of olivine, Ca-rich pyroxene and plagioclase. Incompatible trace-element data from nearby Middle Jurassic basalt lavas (from Kirwanryggen and Heimefrontfjella) suggest a different source and REE modelling indicates generation from garnet lherzolites.
Keywords: Dronning Maud Land; NARE 1976/77; geokjemi; geologi; mineralogi; paleontologi; petrografi

Levels and interactions of heavy metals in sea birds from Svalbard and the Antarctic - Norheim, Gunnar (Environmental Pollution (Barking, Essex: 1987), 1987)
Samples of liver and kidney from 92 seabirds of ten species collected on Spitsbergen and in the Antarctic, were analysed for their content of copper, zinc, cadmium, lead, mercury and selenium. Significantly higher levels of copper and zinc were observed in birds from Spitsbergen than in those from the Antarctic, while the opposite was true for selenium. The highest cadmium levels were found in fulmar Fulmarus glacialis and macaroni penguin Eudyptes chrysolophus. A possibility of kidney damage due to cadmium exists. The highest mercury levels were recorded in brown skua Catharacta lonnbergi collected at Bouvetøya. Lead was not detected in any of the birds. Significant correlations were observed between levels of several of the metals studied, especially between cadminum and zinc and between mercury and selenium. However, for all birds, the highest correlation coefficients were observed when the molar concentrations of cadmium plus mercury, and selenium plus zinc, were used in the calculations. Thus several protective mechanisms may operate to diminish effects of heavy metal contaminants.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; NARE 1978/79; forurensning; fugler; miljøgifter; ornitologi

Hydrolysis of proteins by peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. The hydrolysis of casein by peptide hydrolases of Antarctic krill, E. superba, has been 2. The peptide hydrolases studied included trypsin-like enzymes, carboxypeptidase A-type of enzymes, carboxypeptidase B-type of enzymes, and an aminopeptidase isolated from Antarctic krill. 3. The trypsin-like enzymes seemed to play a decisive role in the degradation of casein, whereas the carboxypeptidase A, carboxypeptidase B and the aminopeptidase had limited effect when acting on casein alone. When combined with the trypsin-like enzymes, the exopeptidases effected enhanced release of amino acids from the protein. 4. Based on the pattern of amino acids relased from casein by a crude extract of krill, and by the isolated peptide hydrolases either alone or in combination, it is concluded that the purified peptide hydrolases examined comprise the major enzymes responsible for the autoproteolytic activity of krill at neutral- to weakly alkaline pH.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

On the purification and characterization of exopeptidases from Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. Two carboxypeptidase-A type of enzymes and two carboxypeptidase-B type of enzymes effecting hydrolysis of Hipp-l-Phe and Hipp-l-Arg respectively, have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. In addition an aminopeptidase has been partly purified. 2. The carboxypeptidases had mol. wts of 27,000 (carboxypeptidase A) and 31,000 (carboxypeptidase B). 3. Carboxypeptidase A exhibited a broad pH optimum with a maximum at pH 5.5–6.5, whereas carboxypeptidase B had a more narrow pH-optimum with a maximum at pH 7. The aminopeptidase had an optimum at about pH 8.7. 4. The carboxypeptidases were inhibited by the chelating agent 1,10-phenanthroline.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Seismic investigations in the Weddell Sea Embayment - Haugland, Kristen; Kristoffersen, Yngve; Velde, Anders (Tectonophysics, 1985)
Keywords: Antarktis; NARE 1976/77; NARE 1978/79; Weddellhavet; ekspedisjoner; seismologi

On the purification and characterization of three anionic, serine-type peptide hydrolases from antarctic krill, Euphausia Superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. Three enzymes effecting hydrolysis of TAME have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. 2. The enzymes had molecular weights of 30,000 (Enzyme I), and 31,000 (Enzymes II and III), respectively, as estimated from SDS-PAGE. 3. pH-optima of about 8.2 were observed for all three enzymes. 4. The enzymes were inhibited by phenyl methyl sulphonyl fluoride (PMSF), tosyl lysyl chloromethyl ketone (TLCK) and soybean trypsin inhibitor (SBTI), whereas tosyl phenyl chloromethyl ketone (TPCK) had no effect on the activity. 5. The enzymes were stable at neutral pH, and only slowly inactivated at highly alkaline pH. Low pH rapidly inactivated all three enzymes. 6. Enzyme I liberated amino acids from casein, whereas Enzymes II and III did not; the latter two being true endopeptidases which effected enhanced amino acid production from casein when mixed with Enzyme I.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Peptide hydrolases of Antartic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. A survey has been made of the peptide hydrolase activities occurring in Antarctic krill, Euphausia superba. 2. A major protein hydrolyzing activity in the pH range of 6–8, and a minor activity at pH 3–4, were detected. 3. Temperature optima of approx. 50°C and 35–40°C, respectively were determined for the neutral and acid peptide hydrolases. 4. Trypsin-like activity, as well as carboxypeptidase A-, carboxypeptidase B-, and aminopeptidase activity were detected in extracts of krill. 5. Considerable variation in total hydrolase activity was observed in different catches of E. superba obtained from the same area. 6. The pattern of release of amino acids during autolytic breakdown of krill proteins was very similar in catches of krill exhibiting considerable differences with respect to total peptide hydrolase activity.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Enzyme polymorphism in Antarctic krill (Euphausiacea); genetic variation between populations and species - Fevolden, Svein Erik; Ayala, Fransisco J. (Sarsia, 1981)
By means of enzyme electrophoretical assays three samples of Euphausia superba, all from the Atlantic sector of the Antarctic Ocean, were examined to see whether or not they represent genetically separated populations. The same samples were also compared with E. superba from off the Western coast of the Antarctic Peninsula, representing the Pacific sector. The latter animals have previously been studied by other authors. One sample of a second species of Antarctic krill, E. crystallorophias, was likewise examined. Thirty-five loci were studied in E. superba, and it is concluded that the three samples from the Atlantic sector most probably do not represent reproductively isolated populations. Their average heterozygosity, about 10%, is however greater than the value previously found for the ‘Pacific’ E. superba, 5.8 %. Calculations of the genetic identity and genetic distance between the Atlantic and ‘Pacific’ samples of E. superba suggest they represent separate populations. The average heterozygosity of E. crystallorophias was estimated to be between 9.1 and 9.4 %, from studies of 33 loci. The genetic distance between this species and E. superba was estimated at 0.989. The results are finally discussed in terms of postulated theories on genetic variability versus environmental heterogeneity.
Keywords: NARE 1976/77; NARE 1978/79; Sørishavet; genetikk; krill; marin biologi; plankton

A new process for the utilization of Antarctic krill - Ellingsen, Trond E.; Mohr, Viggo (Process Biochemistry, 1979)
Keywords: NARE 1976/77; Sørishavet; biokjemi; krill; lyskreps; marinbiologi; plankton

Investigations on krill (Euphausiacea) sampled during the Norwegian Antarctic Research Expedition 1976–1977 - Fevolden, Svein Erik (Sarsia, 1979)
Krill was sampled in the Weddell Sea, farther south than ever before, and off Bouvet-öya. Five species were found: Euphausia superba, E. crystallorophias, E. frigida, E. triacantha, and Thysanoessa macrura. E. superba and E. crystallorophias were the most abundant species north and south of 74° S respectively. Length frequency analyses suggest that E. superba from the inner Weddell Sea takes three years to reach maturity. This population differed in several aspects from the populations farther north. E. crystallorophias and T. macrura were registered south to 77°45′ S, the southernmost localisation investigated. The material gives no clear evidence whether these species take one or two years to reach maturity. Their spawning activity seems to start earlier in the season than for E. superba. E. frigida and E. triacantha were only-found off Bouvetöya. Continuous echosounder recordings revealed that the total abundance of krill in the southern parts of the Weddell Sea was low, as was also the abundance on the route between the South Orkney Islands and Dronning Maud Land.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; Sør-Orknøyene; Sørishavet; Weddellhavet; dyreplankton; krill; plankton; zooplankton

Mesozoic palaeomagnetism in Vestfjella, Dronning Maud Land, East Antarctica - Løvlie, Reidar (Geophysical Journal of the Royal Astronomical Society, 1979)
Thermal and alternating field demagnetization of oriented samples of Mesozoic lava flows (200–230 Myr) and dykes (154–172 Myr) collected from seven nunataks within the Vestfjella region, Dronning Maud Land, revealed stable directions of magnetization of normal and reverse polarity. Directional distributions of both polarities define tight groups along the same palaeomagnetic axis. Depending on whether the regional westward dip of the lava flows originated prior to, or after the intrusive igneous phase, two or one, respectively, palaeomagnetic pole(s) can be estimated. Both poles, however, are in general accord with previous Mesozoic poles from East Antarctica.
Keywords: Dronning Maud Land; NARE 1976/77; geofysikk; geologi

Ice-shelf underwater morphology - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: Antarktis; NARE 1976/77; ekspedisjoner; forskning; glasiologi; isshelf; morfologi

Plough marks in the Weddell Sea - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; forskning; havbunnen; oseanografi

De norske Antarktis-ekspedisjonene 1976-77 og 1978-79: biologiske undersøkelser på Bouvetøya og i havet - Sømme, Lauritz; Fevolden, Svein Erik (Det norske videnskaps-akademi. Årbok, 1979)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biologi; geografi

Basaltene i Vestfjella og Gondwanalands historie - Furnes, Harald (Naturen, 1978)
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; forskning; geokjemi; geologi; petrologi

Hva den fossile magnetiseringen i Vestfjella kan fortelle - Løvlie, Reidar (Naturen, 1978)
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; forskning; geologi; jordmagnetisme

Om Antarktis, isfjell og havnivå - Maisey, George H (Naturen, 1978)
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; geologi; havbunnen; topografi

Hvorfor er de Antarktiske isfjell så store? - Orheim, Olav (Naturen, 1978)
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; glasiologi; innlandsis; isbreer; isfjell; isshelf; kalving; topografi

Cold-Hardiness of Cryptopygus antarcticus (Collembola) from Bouvetøya - Sømme, Lauritz (Oikos, 1978)
Cryptopygus antarcticus Willem were extracted from samples of mosses collected at Bouvetøya during the Norwegian Antarctic Expedition in February 1977. The body length of the collembolans from these samples ranged from 225 to 1125 μm. The collembolans had average supercooling points between -24° and -26°C. Acclimation at -5°, 0° and 12°C for various time intervals had no significant effect on their ability to supercool. Glycerol was not found in specimens acclimated at -5° and 0°C. All specimens were killed by freezing at temperatures in the range of their supercooling points. Chill-coma temperatures of the collembolans were between -2° and -7°C.
Keywords: Bouvetøya; NARE 1976/77; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Antarktisekspedisjonen 1976/77 - Hjelle, Audun; Snuggerud, John (Amatørradio, 1977)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; ekspedisjoner